Torque characteristics of the revolving vane air expander - Aw, Kuan Thai (2021)
The use of compressed air as an alternative source of clean energy requires an air expander to extract work. A new design, known as the revolving vane mechanism, has been proposed in an effort to develop high efficiency rotary machines. This paper provides an in-depth analysis by including the vibration characteristics of the revolving vane air expander to evaluate the steady-state operating output torque. A generic model for describing the revolving vane rotational vibration is first derived and subsequently modified to describe the prototype tested. Measurements show that the output torque is bimodal; arising from a tolerance gap between the vane and its slot during fabrication. This effect was found to be less pronounced at high operating speeds. The model is found to be in good agreement with the measured output torques. Further analysis with the validated model showed that extracting shaft work from the cylinder would result in better performance.